Entrepreneurship Dalam Menyikapi Dunia Nyata - Harfandi, Harfandi; Putri, Hesi Eka (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2009)
In the real life, at the see more scarcity at hte job vacancy for the labour force, it's the effect to create many unemployment. It is not only to elemtary and high education but also the diploma and graduate aducation. For that, need to aplication and growing up characteristic the entrepreneurshhip in the self student. So, after they finish from collage, they can create to job vacancy not they are job seekers.